Analisis Pengaruh Sosial Media Instagram Terhadap Perkembangan Usaha Mikro, Kecil, dan Menengah Coffee Shop di Yogyakarta - Pangestu, Oby; El Hasanah, Lak Lak Nazhat (Jurnal Aplikasi Bisnis, 2023)
The rapid development of the economy and communication technology provide various conveniences in the business world. It is hoped that the use of digital technology-based marketing concepts will provide direction for Micro, Small, and Medium Enterprises to further develop and become the center of strength of Indonesian economy. One of the media used is the Instagram application. Numerous coffee shops in Yogyakarta use Instagram as their main benchmark in terms of marketing. The purpose of this study was to analyze the effect of e-WOM, content and promotion on the development of MSMEs, especially coffee shops in Yogyakarta. The samples used in this study were from Micro, Small and Medium Enterprises Coffee shops in Yogyakarta. Methods of data analysis were descriptive statistical analysis and logistic regression analysis. The results of this study indicated that the variables e-WOM, Content, and Promotion have a positive effect on Business Development.